Differentiated marketing strategies between strategic groups in Greek food industry. (9th December 2014) - Notta, Ourania
This study examines the heterogeneity of the Greek dairy industry based on 'strategic group theory'. Its objectives are: (1) to define strategic groups within the Greek dairy industry; (2) to examine whether firms move between strategic groups over time and (3) to examine the performance differences among these strategic groups. I use as key strategic variable product differentiation, which is measured by both advertising intensity and number of brands per firm. The results for the period 2002–2011 prove the existence of three strategic groups, based on differentiation within the Greek dairy industry, with certain performance differences.